2021
DOI: 10.9734/acri/2021/v21i130227
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact Assessment of Vehicular Traffic along Major Roads in Delta State of Nigeria, Using Contamination and Enrichment Factors

Abstract: This research was carried out to evaluate the impact of vehicular traffic, on the soil and grasses growing along major roadsides in Delta state, Nigeria. Soil and Guinea grass samples were collected from three major roads, and a control point in Delta State. The collected samples (plant and soil) were digested according to standard procedures, and their heavy metals (Fe, Cu, Pb and Ni) concentrations were analyzed by using the Atomic Absorption Spectrophotometry. Results obtained indicated that the soil and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another study pointed out that the Pb concentration in the leaves of Ficus religiosa increased up to 14,100 ppb, and the correlation analysis pursued by the authors revealed a robust correlation between traffic density and Pb accumulation in plants (Agrahari et al 2018). In many studies it has been confirmed that Pb concentration increases depending on traffic density (Al-Shidi et al 2020, Juwah and Tachere 2021, Soba et al 2021.…”
Section: Discussionmentioning
confidence: 95%
“…Another study pointed out that the Pb concentration in the leaves of Ficus religiosa increased up to 14,100 ppb, and the correlation analysis pursued by the authors revealed a robust correlation between traffic density and Pb accumulation in plants (Agrahari et al 2018). In many studies it has been confirmed that Pb concentration increases depending on traffic density (Al-Shidi et al 2020, Juwah and Tachere 2021, Soba et al 2021.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the overflow of hazardous wastes such as toxic liquids and gases, which can pollute drinking water, reduce soil quality, and release toxins in the air, industries has become very important in terms of environmental degradation (Hanfi et al, 2020). Juwah and Tachere, (2021) highlighted vehicular emissions as a major source of heavy metal pollution has negative effects on the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Metal contamination causes variation in plant growth and physiology of roadside plants. Leaves of roadside plants area reservoir for noxious emission through vehicles (Juwah and Tachere, (2021). Plants growing on metal-contaminated sites exhibited metabolic changes, reduced growth, reduced biomass production, and reduced metal accumulation.…”
Section: Introductionmentioning
confidence: 99%